Comparative Study: Teaching Expriences of Prospective Teachers before and After Participating in the Teacher Professional Education Program at UMS Rappang - Aswadi Aswadi; Sam Hermansyah; Andi Sadapotto; Buhari Buhari; Ibrahim Manda; Syamsu T; Muhammad Hanafi; Jusrianto Jala; Amalia Amalia (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to compare the teaching experiences of prospective teachers before and after participating in the Teacher Professional Education Program (PPG) at UMS Rappang. The research utilizes a qualitative descriptive method, collecting data through interviews, observations, and document analysis. Findings indicate significant improvements in pedagogical skills, classroom management, and teaching confidence after the completion of the PPG program. The study highlights the role of professional education in preparing teachers for effective classroom practice and fostering a deeper understanding of teaching methodologies. These findings suggest that PPG plays a vital role in shaping competent and professional educators